Childhood Blindness: Beyond VISION 2020 and the COVID-19 Pandemic - Roland Joseph D. Tan MD, MS; Indra Prasad Sharma MOptom; Don Eliseo Lucero-Prisno MD, PhD (SAGE Publishing, 2021)
The World report on vision in 2019 found it difficult to evaluate VISION 2020's impact on childhood blindness and VI since data on prevalence and causes were scarce. Considering the high chance of the global initiative missing its desired goal in children, we recommend that a sustainable version of it be launched soon. Central to this new initiative shall be better data collection on prevalence and causes of childhood blindness and VI, eye care provision and an updated and uniform system of reporting. Complete and updated data can better reflect the burden and monitor the impact of interventions. However, data collection will continue to be difficult due to the COVID-19 pandemic so the initial phase shall be tailored to the current situation.